THE SOCIO-ECONOMIC CONDITION OF THE TURKESTAN REGION DURING THE FIRST WORLD WAR - Tugalova Madina Erkin qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the socio-economic and political situation in the Turkestan region during the years of the First World War (1914–1918). Drawing on historical documents, archival records, and secondary sources, the study investigates how the global conflict impacted the daily life, economy, and governance of the region under  Russian  colonial  rule.  Special  attention  is  paid  to  the  1916  uprising,  forced conscription, and growing social tensions that eventually contributed to anti-colonial sentiments.